(untitled) (La U Investiga, 2018)
The objective of this study, among others, was to determine the level of food insecurity and to evaluate the nutritional status through anthropometric and dietary surveys, as well as to identify certain diseases in children under five years of age. The study was conducted under descriptive and transversal conditions; from October 2017 to February 2018; it covered 78 families. The techniques used were mostly surveys that dealt with the following issues: socio-demography, ELCSA, anthropometry, frequency of food consumption and processed in SPSS. Results: 29% of the population showed severe food insecurity; only 5% of the surveyed families do not live in food insecurity. Child nutrition assessment, according to WHO standards, points at poor nutrition levels. In regarding to Weight / Size ratio, a 2% presents wasting, and a 6% risk of wasting. In the same way, as for Size - Length / Age ratio, 29% of the study population, presents growth retardation. The Weight / Age ratio shows an 4% as low weight, and 8% as having low weight risk. The BMI / Age ratio presents overweight and obesity in a 9%, and a 10% as overweight risk. There is a IRA predominance in a 25%. In adults, there is high prevalence of overweight and obesity in a 62% based on BMI measurements, and a 79% regarding fat percentage. The food-consumption frequency survey identified cereals and derivatives as the most consumed foods; it presented chicken as the main source for protein, palm oil as the lipid source and seasonal fruits as the major source for vitamins. The low consumption of vegetables was notorious. Conclusions: El Juncal community presents considerable levels of food insecurity and there are also problems of malnutrition both in children and in adults.